PENGEMBANGAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA VISUAL POSTER DALAM PEMBELAJARAN MENULIS TEKS PERSUASI - Athoillah, Ujang Ahmad; Wikanengsih, Wikanengsih; Yani, Aurelia Sakti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
One alternative learning model in the 2013 curriculum is Discovery Learning (DL). Nowadays, the facts in the field of teachers have never developed a discovery learning model to improve students' abilities, which tend to be low. Discovery learning as a teaching procedure that emphasizes individual teaching, object manipulation, etc. is expected to be a solution for teachers in teaching knowledge to their students. The method used in this research is qualitative with a descriptive approach. Data collection used is literature study, observation, interviews and in-depth analysis of documents related to research. The purpose of this study was to determine the development design of the discovery learning model assisted by visual poster media in the learning of writing persuasion texts with the object of research of grade VIII students. The results found in this study are that the first step in the discovery learning model is to display a poster containing an advertisement in the form of an image, which is a stimulus or stimulus for students to start learning activities and get to know the material to be taught. The next step is that students are required to identify problems that have been presented and have been observed first. Next, students collect data that has been seen, observed, and from their own knowledge to solve problems from the results of their collection and knowledge. The data will later be used to answer the problem. from the identification of the observed problems. Then, students verify or prove whether the resulting data can solve the problem from the identification results or not. The final step is to draw conclusions from temporary answers, Then in the design of the discovery learning model development assisted by visual media posters is to prepare the material to be presented in advance, making learning scenarios using the discovery learning model, and preparing questions or assignments that students must do after learning activities with the discovery learning model, and the obstacles that students experience in writing persuasion texts are in terms of making paragraphs or paragraphs in the form of persuasion (solicitation, seduction, or persuasion. ) including students experiencing obstacles in arranging the flow of text from the material presented in the form of posters.